2013
DOI: 10.1002/cb.1409
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty in ethical consumer choice: a conceptual model

Abstract: The market place has seen significant growth in the demand for 'ethical' products and services. Yet, consumers often experience knowledge, evaluation and choice uncertainties in decision-making processes, particularly in relation to products such as ethical clothing. The authors explore this pertinent form of consumer uncertainty through three qualitative studies of ethical consumers that examine their approaches to clothing consumption. In-depth interviews and focus groups confirm uncertainty arises; the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 52 publications
2
56
1
1
Order By: Relevance
“…Our respondents appear to suffer none of the anxiety found by Longo, et al (2017) and Connolly and Prothero (2008), nor the sacrifice (Johnstone and Tan, 2014), guilt (Bray et al 2011), conflict (Hassan et al 2013) or contradiction (Littler 2011) identified by others. We find evidence for Dewey's (1939) assertion that morality is shaped by ends-in-view which are ideational (connecting valuation with desire and interest) and which are determined reciprocally and recursively via means of action that are often entrenched in habits.…”
Section: Concluding Discussion: Everything Flowsvalue and The Consummmentioning
confidence: 52%
See 2 more Smart Citations
“…Our respondents appear to suffer none of the anxiety found by Longo, et al (2017) and Connolly and Prothero (2008), nor the sacrifice (Johnstone and Tan, 2014), guilt (Bray et al 2011), conflict (Hassan et al 2013) or contradiction (Littler 2011) identified by others. We find evidence for Dewey's (1939) assertion that morality is shaped by ends-in-view which are ideational (connecting valuation with desire and interest) and which are determined reciprocally and recursively via means of action that are often entrenched in habits.…”
Section: Concluding Discussion: Everything Flowsvalue and The Consummmentioning
confidence: 52%
“…Hassan et al (2013) and Schröder and McEachern (2004), for example, describe contradictions that arise from guilt and the breaking of ethical rules. McGoldrick and Freestone (2008) argue that we accrue a 'balance sheet' of gains and losses that are in opposition, and state consequently that this represents a conflict to be resolved.…”
Section: Trade-offs In Ethical Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are prepared to go to great pains to find precisely the right sort of product. If they do not find what they believe is the perfect commodity they put off the purchase (Hassan et al, 2013). They acquire information from the media and justify their choices with the views of experts in the various sectors.…”
Section: The Uncompromisingmentioning
confidence: 99%
“…Thus, the decision-making process becomes more complex as tourists must choose from this variety. At the same time, Hassan, et al (2013) point out that consumers are uncertain as to both the information available to make their choice and the means for evaluating their decisions when making a decision. Furthermore, consumers are often forced into a dynamic search while under conditions of extreme time pressure and choice overload (Reutskaja, Nagel, Camerer, & Rangel, 2011).…”
mentioning
confidence: 99%